2013
DOI: 10.1080/09583157.2012.748183
|View full text |Cite
|
Sign up to set email alerts
|

The effects of periodic warming on the survival and fecundity ofDiadromus pulchellusduring long-term storage

Abstract: Biological control strategies capitalise on natural mechanisms such as predation and parasitism to reduce the need for chemical applications to control insect pests. In Canada, the parasitic wasp Diadromus pulchellus Wesmael (Hymenoptera: Ichneumonidae) is being investigated for its use in the biological control of an invasive crop pest, the leek moth, Acrolepiopsis assectella (Zeller) (Lepidoptera: Acrolepiidae). Large numbers of insects will be needed for releases to ensure that populations of D. pulchellus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In another case, FTR slightly reduced adult longevity (Ismail et al, 2013), which could reduce lifetime fecundity if that species continues to reproduce throughout the adult stage. However, in another study using Diadromus pulchellus, there was no effect of FTR on the number of mated females or fecundity compared with CLT (Murdoch et al, 2013). The rationale for the existence of a fitness cost is that, during recurrent warm periods of FTR, the overshoot in metabolic rate (Lalouette et al, 2011;Yocum et al, 2011;Boardman et al, 2013) may progressively consume more energy stores than under CLT.…”
Section: Downsides To Ftrmentioning
confidence: 98%
“…In another case, FTR slightly reduced adult longevity (Ismail et al, 2013), which could reduce lifetime fecundity if that species continues to reproduce throughout the adult stage. However, in another study using Diadromus pulchellus, there was no effect of FTR on the number of mated females or fecundity compared with CLT (Murdoch et al, 2013). The rationale for the existence of a fitness cost is that, during recurrent warm periods of FTR, the overshoot in metabolic rate (Lalouette et al, 2011;Yocum et al, 2011;Boardman et al, 2013) may progressively consume more energy stores than under CLT.…”
Section: Downsides To Ftrmentioning
confidence: 98%
“…Ismail et al (2010) did not observe any fecundity decrease after FTR exposition in Aphidius ervi females. Likewise, Murdoch et al (2013) tested the effect of warming interruptions applied once or thrice during a cold storage period of 8-week and found no differences between constant or fluctuating storage on fecundity of the leek moth Diadromus pulchellus. Allocation of limited energy often results in life-history trade-offs, for instance between reproduction and longevity (Zera & Harshman, 2001;Attisano et al, 2012).…”
Section: Impact Of Ftr On Life History Traitsmentioning
confidence: 99%
“…Compared to STR, FTR has been associated with lower lipid content, body mass, fecundity, and longevity of some insects ( Carroll and Quiring 1993 ; Ismail et al 2010 ; Marshall and Sinclair 2010 ; Basson et al 2012 ). For other insects, no differences in fecundity ( Murdoch et al 2013 ) or flight performance and metabolism ( Bennett et al 2013 ) have been observed. Comparative studies that track macronutrient stores through overwintering may help us better understand the net benefits and costs of FTR and the role nutrition plays in overwintering success.…”
mentioning
confidence: 95%